Acute Submassive Pulmonary Embolism Following Varicose Vein Surgery in a Patient Receiving Hormonal Replacement Therapy - Nishibe, Masayasu (The Editorial Committee of Annals of Vascular Diseases, 2010)
Acute pulmonary embolism following varicose vein surgery is reported in a patient receiving hormonal replacement therapy. A 45-year-old woman underwent partial stripping of the greater saphenous vein of her bilateral legs and division of the lesser saphenous vein of her left legs under spinal anesthesia. On the first postoperative day, she complained of severe chest discomfort and collapsed suddenly while walking to the toilet. Emergency spiral computed tomography and perfusion scintigraphy demonstrated multiple defects in the bilateral lower lobes. She recovered after aggressive anticoagulant therapy. Although acute pulmonary embolism occurs only rarely after varicose vein surgery, it is important to remember its possibility especially when a patient has known risk factors predisposing venous thromboembolism, such as hormone replacement therapy.